Physicochemical and adsorption properties of guava leaves-activated carbon by hydrochloric acid on adsorption of methylene blue / Mohd Fauzi Abdullah and Nur Fazilah Othman - Abdullah, Mohd Fauzi; Othman, Nur Fazilah (Universiti Teknologi MARA Shah Alam, 2023)
This study emphasizes the biomass waste which is dried guava leaves as a natural low-cost adsorbent precursor of activated carbon for methylene blue (MB) dye solution due to its high abundance and availability in Malaysia. MB dyes which were largely consumed by the textiles industry pose several hazardous complications on human health without proper wastewater treatment. Thus, adsorption for water treatment serves as a cost-effective method to adsorb the dyes using low-cost adsorbent from dried leaves biomass. The dried leaves underwent chemical activation with hydrochloric acid (HCl) with ratio 1:1 and were carbonized at 700 °C for an hour and then neutralized for characterization and batch adsorption study. The physicochemical properties of guava leaves HCl activated carbon (GL-HAC), was characterized using ash content, moisture content, bulk density and iodine number. Percentage yield of GL-HAC was apparently high at 89.90 %. The GL-HAC reported had relatively low percentage of ash content and moisture content. The bulk density of the activated carbon was also low at 1.6 g/mL. The iodine number was calculated at 339.9 mg/g. The pHPZC for GL-HAC was obtained at 4.3 indicating that this activated carbon is efficient for the removal of MB dye with the pH solution above the pHPZC value. The results of the FTIR study shows that the functional groups of hydroxyl, amine, carbonyl, and carboxylic acid are present in GL-HAC. Batch adsorption studies were carried out to determine the most favourable condition for the activated carbon to adsorb methylene blue dye. The operating variables studied were adsorbent dosage, initial pH of solution, initial dye concentration and contact time. The results revealed that the effect of initial concentration and contact time were directly proportional to the adsorption capacity of MB dyes on the activated carbon. Thus, this study has demonstrated the potential of dried guava leaves as low-cost precursor of activated carbon for the removal of MB dyes.